SCIENTIFIC AND THEORETICAL ANALYSIS OF AGGRESSION IN STUDENTS OF MIDDLE SCHOOL AGE - Болтаев Аъзам Акрамович, Оманова Севара Ғайратуллаевна (Journals Park Publishing, 2023)
The school was attended by students studying at a special workplace and studying at the workplace. The volleyball school is a research center. As a trainer engaged in the preparation, preparation and conduct of trainings on the basis of special training and preparation.
Keywords: Schoolchildren, agility development, young athletes, special exercises, research, experience and control group.